African co-operatives and efficiency - Widstrand, Carl Gösta.; Ghai, Yash P. (Uppsala : Scandinavian Institute of African Studies, 1972)
The purpose of this paper is to provide some topics for discussion concerning the problems of efficiency in cooperatives, such as "why is efficiency important?" "how does it relate to other goals that co-operatives try to achieve?" and "what factors determine efficiency in co-operatives?".
Introductory papers sent to the participants before a seminar held at the Co-operative College, Langata, Kenya, 29 Nov.-4 Dec., 1971.
Includes bibliographical references.
ne 25/01/2019
Loans
Keywords: Cooperatives